Development and in vitro evaluation of bilayer tablets having an immediate release layer containing donepezil hydrochloride and an extended release layer containing memantine hydrochloride - (:unkn) unknown (Polish Pharmaceutical Society, 2018)
The aim of this study was to develop a bilayer tablet that can be administered in a conventional dosage form, but includes two different active pharmaceutical ingredients one of which was Donepezil hydrochloride (HCl) and was available as an immediate release layer and the other which was Memantine hydrochloride (HCl) and was available as an extended release layer. The development process of bilayer tablets consisted of three steps: the formation of two separate tablets having different active moieties; the design of the formulation and analytical methods according to the targeted dosage form; and finally the preparation of an optimum formulation having preferred release profiles. In the design of the formulation step, initially, the extended release layer of bilayer tablets was studied. 13 different formulations were prepared for the extended release layer using several production techniques, different polymer types with various molecular weights, and different compositions of selected polymers. Each formulation was examined in terms of physical characteristics and dissolution profiles. Later, two different formulations were prepared for the immediate-release phase using a direct compression method to consider the time and cost of the manufacturing process. Formulations which had the best results as separate tablets were selected for the preparation of final bilayer tablets. Thus, we had the chance to evaluate the effects of various polymer types, effects of a combination of polymers having different release control properties, effects of polymers with different molecular weights, and effects of the production process on the dissolution profiles of bilayer tablets having one immediate-release and one extended release layer. To our knowledge, it was the first time that we prepared bilayer tablets of donepezil hydrochloride and memantine hydrochloride having two different dissolution profiles. © 2018 Polish Pharmaceutical Society. All Rights Reserved.
Keywords: Alzheimerís; Bilayer tablets; Controlled release tablet; Donepezil HCl; Immediate-release tablet; Memantine HCl